A Corporate Strategy for AIROD Sendirian Berhad (1988 - 1994) - Taib, Muhamed Ghazali (1988)
AIROD Sendirian Berhad (ASB) was incorporated in early 1985 as a business firm, being the first Government project to be privatized. Its principal activities range from providing overhaul and repair services of military and commercial aircrafts and its related equipment and components. ASB clearly set its short-term and long-term goals and are made known to all its employees. Its organization structure is based on seven formal departments under the overall direction of the Managing Director, an expatriate from Lockheed Aircraft Services International (LASI). The main problems faced by this company are: its inability to penetrate open market; high overhead costs; and inadequate skill and expertise to keep in pace with the rapidly changing environment of aircraft maintenance services.